A Combined Treatment Approach to Support Everyday Function and Promote Brain Health in Older Adults: A Pilot Study. Issue 2 (3rd March 2020) - Denny, Katherine G.; Harvey, Danielle; Meyer, Oanh L.; Chan, Michelle L.; Barba, Cheyanne; Farias, Sarah Tomaszewski
ABSTRACT: Objective : Subtle changes in functional abilities are an early indicator of cognitive impairment. Early intervention may be key to prolonging independence. This study describes the development and program evaluation of an intervention designed to (1) bolster the use of compensation strategies that support everyday executive and memory functioning and (2) utilize these strategies to promote engagement in brain health activities. Method : Older adults (n = 35) with subjective cognitive complaints completed an eight-week group program targeting compensation strategies (e.g., calendars) and brain health activities (e.g., physical exercise). Participants completed outcome measures at first, last, and 3 month follow-up sessions. Results : Compensation strategy use can be successfully taught to and implemented by older adults, and increasing engagement in brain health behaviors is possible, although particular lifestyle changes are challenging to implement. Conclusion : Findings support the use of interventions aimed at increased engagement in compensation strategies to aid everyday memory and executive functioning. Clinical Implications : Early intervention may help to promote prolonged functional independence.